The Relationship between Environmental Factors during the Rainy Season and Un-opened Floret Yellowing in Dendrobium Sonia ‘Ear-Sakul’ - Vimolchat Sarntinoranont; Surawit Wannakrairoj (Agriculture and Natural Resources, 2010)
The pre-harvest yellowing in the un-opened florets of Dendrobium Sonia ‘Ear-Sakul’ grown under 50% shade in a saran-house was studied. In the rainy season, the most sensitive period for yellowing in un-opened florets was found to be the ready-to-bloom stage. The highest percentage of inflorescence with un-opened floret yellowing was obtained from those with no open florets. The percentage of inflorescence with yellowed un-opened florets could be predicted (R2= 0.613) using an environmental model consisting of: 1) cumulative hours of daytime with 0 μmol m-2s-1 light intensity; 2) average rainfall during 1000-1400 hours; 3) cumulative hours of daytime with the temperature less than 25°C; and 4) cumulative hours when the relative humidity (RH) was in the range 75-90% in the period 3 d before un-opened floret yellowing. The developmental stage of inflorescence did not affect un-opened floret yellowing. The simulated stress environment of the rainy season had no effect on the sucrose, glucose and fructose contents in the first- and second-largest un-opened florets, nor on the calcium and boron contents in the inflorescence and leaves. Under the simulated stress environment of the rainy season in a growth chamber, spraying 1% sucrose solution might be useful to reduce yellowing in un-opened florets.